Impact of exercise selection on hamstring muscle activation. Issue 13 (13th May 2016) - Bourne, Matthew N; Williams, Morgan D; Opar, David A; Al Najjar, Aiman; Kerr, Graham K; Shield, Anthony J
Abstract : Objective: To determine which strength training exercises selectively activate the biceps femoris long head (BFLongHead ) muscle. Methods: We recruited 24 recreationally active men for this two-part observational study . Part 1: We explored the amplitudes and the ratios of lateral (BF) to medial hamstring (MH) normalised electromyography (nEMG) during the concentric and eccentric phases of 10 common strength training exercises. Part 2: We used functional MRI (fMRI) to determine the spatial patterns of hamstring activation during two exercises which (1) most selectively and (2) least selectively activated the BF in part 1. Results: Eccentrically, the largest BF/MH nEMG ratio occurred in the 45° hip-extension exercise; the lowest was in the Nordic hamstring (Nordic) and bent-knee bridge exercises. Concentrically, the highest BF/MH nEMG ratio occurred during the lunge and 45° hip extension; the lowest was during the leg curl and bent-knee bridge. fMRI revealed a greater BF(LongHead) to semitendinosus activation ratio in the 45° hip extension than the Nordic (p<0.001). The T2 increase after hip extension for BFLongHead, semitendinosus and semimembranosus muscles was greater than that for BFShortHead (p<0.001). During the Nordic, the T2 increase was greater for the semitendinosus than for the other hamstring muscles (p≤0.002). Summary: We highlight the heterogeneity of hamstring activation patterns in different tasks. Hip-extension exercise selectively activates the long hamstrings, and the Nordic exercise preferentially recruits the semitendinosus. These findings have implications for strategies to prevent hamstring injury as well as potentially for clinicians targeting specific hamstring components for treatment (mechanotherapy).